Development of Arabic Learning Media Innovation from Neuroscience Perspective for Santri: Implications in the Development of Intellectual Property Rights in Islamic Boarding Schools - Mohammad Jailani (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
This study aims to develop (1) Arabic learning media innovation with a neuroscience approach at the Babul Ulum Islamic Boarding School Pamekasan; and (2) the factors that become obstacles in learning Arabic at the Babul Ulum Islamic Boarding School in Pamekasan. (3) knowing the needs analysis of ustadz for neuroscience media, (4) designing neuroscience media prototypes, (5) analyzing the results of expert validation and revision of neuroscientific media prototypes, (6) analyzing the RND of previous learning with neuroscience media to be conveyed to students at Islamic boarding schools Babul Ulum Pamekasan. The population that was taken as the research sample by the researcher was 20 students and 1 teacher teaching Arabic. This research is research and development research. The research has been conducted on-site case studies and adapted the Rnd reference literature. The procedure for this research phase refers to the theory of Rnd Borg and Gall which was developed by Sugiyono, namely 10 steps. However, with limited time, the researcher only took 5 steps The subjects of this research are ustadz and santri in Islamic boarding schools. The results of this study are (1) research by the ustadz require the development of neuroscience media to be implemented in Arabic learning. (2) neuroscience media prototypes in the form of audio-visual learning videos that are conceptualized with interesting audio and visualizations, containing media delivery, product specifications, Arabic text, mufrodat, and muhadasah materials, operating procedures, implementation steps for using learning media, and developer profiles. (3) the results of expert validation include aspects of content/material feasibility, language feasibility aspects, presentation feasibility aspects, and graphic aspects with an overall average value of 88.21 with a very decent category, (4) neuroscience media as a means of audio-visual media emphasizes and directs santri to learn Arabic with a brain approach, stimulation from the brain as the central neuron for the growth of intelligence.